Telemedicine in neonatal care-Saving lives with technology! - Ahmed, Shahamah (Journal of the Pakistan Medical Association, 2022)
Madam, neonatal mortality in Pakistan i.e. death of babies within first twenty eight days of life is 49 per 1000 live births. Moreover, Pakistan contributes to 7% of global neonatal deaths. (1) Cause of mortality may be infection, intra-partum complications, prematurity or congenital birth defects but there is one thing common in all; majority of them occur in rural population due to lack of access to health care facilities. (2) With recent advances, role of tele-medicine has proved to be a milestone in field of medicine especially in underdeveloped and rural areas. According to World Health Organization (WHO), Telemedicine is defined as affordable use of Information and Communication Technology (ICT) for provision of health facilities and care. (3) A study done in Karachi in early 2020 by Ashfaq A et al showed average knowledge of telemedicine among clinicians and junior doctors, but we are still hopeful that since after the global pandemic of COVID-19, not just this knowledge has improved but also perceptions regarding telemedicine should have changed (4). In another study done in china by Makkar A. et al, they demonstrated the role of tele-medicine in not just tele-rounds of NICU but also successful e-examinations of Retinopathy of prematurity, tele-echocardiography, tele-NPR guidance to healthcare providers and family support. Moreover, home based care can be efficiently provided to preterm low birth weight babies including establishment of enteral feeding. (5) With a global shortage of physicians worldwide, lack of neonatologists is a major reason of neonatal referrals from rural areas and tele-medicine can give promising results in this regard. It can not only prevent unnecessary ambulation of tiny patients but also improve survival and quality care. Though under umbrella of private NGOs, tele-medicine is being started for satellite centers in few regions of country but obviously it doesn’t cover majority of population. It is high time to realize importance of Tele-medicine in periphery care setups. Though provision of equipment, installments of high quality ICT and infrastructure might seem a barrier in establishment of Tele-medicine but it can bring revolutionary improvement in neonatal care. It cannot just help reducing over burdening to tertiary care hospitals but also in avoiding hazards and cost of patient transfer.